Vietnam, the ten thousand day war - Basehart, Richard, 1914-1984.; Arnett, Peter, 1934-; BWE Video (Firm) (Salt Lake City, Utah : Bonneville Worldwide Entertainment, 1998)
Presents the real story behind the longest, most controversial war in modern history. Using film clips shot by both sides and seen through the eyes of policymakers and combat veterans, the programs reexamine without blame or judgment the rise and fall of America's twenty-year commitment to the war in Vietnam.
1. America in Vietname -- 2. Days of decision -- 3. The guerilla society -- 4. Tet! -- 5. Soldiering on -- 6. Peace.
LIBRARY HAS DVD COPY FOR CLASSROOM USE.
Narrator, Richard Basehart.
VHS.
Keywords: Documentary films; Vietnam War, 1961-1975.; Vietnam -- History -- 1945-1975.; Vietnam -- Foreign relations -- United States; United States -- Foreign relations -- Vietnam; Vietnam -- History -- 1975-